2000
DOI: 10.1007/s10434-000-0346-9
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cancer in Young Patients: Demographic, Clinicopathological, and Prognostic Factors in 92 Patients

Abstract: The high frequency of a positive family history in young patients suggests an opportunity to identify a high-risk population for screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
88
2
22

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(132 citation statements)
references
References 16 publications
20
88
2
22
Order By: Relevance
“…Our patients under 30 years old were much younger than those of other reports, which dealt the age of under 40 [9][10][11][12]15,18 or 35 13,14 years as the young group. Therefore, our present materials are considered to be more suitable for analysis of carcinogenesis of cancer in young patients.…”
Section: Intramucosal Gastric Cancer In the Youngcontrasting
confidence: 55%
See 1 more Smart Citation
“…Our patients under 30 years old were much younger than those of other reports, which dealt the age of under 40 [9][10][11][12]15,18 or 35 13,14 years as the young group. Therefore, our present materials are considered to be more suitable for analysis of carcinogenesis of cancer in young patients.…”
Section: Intramucosal Gastric Cancer In the Youngcontrasting
confidence: 55%
“…In several studies, the clinicopathological features of gastric cancer in the young were somewhat different from ours. 1,2,[9][10][11][12][13][14]3,[15][16][17][18][19] With regard to histological type, poorly differentiated adenocarcinoma tends to be more frequent in young adults, [12][13][14]3 however, there is no difference in sex distribution between the young and elderly patients. 9,10,13,14 The discrepancy (b) Fifty-seven-year-old male subject (same case as a).…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have reported that cancers are located in proximal (Koea et al, 2000;Lim et al, 2003) or middle (Nakamura et al, 1999) parts of the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Even though we are not able to verify the exact evidence of these findings, this corresponds to previous reports that the predominance of signet ring cell in young gastric cancer patients (68% in 92 patients, 40 years of age or younger). 4 Unlike the characteristics of advanced-stage cancer patients, the percentage of tumors located in the lower third for patients at the early stage were 71.9%, which was higher than that reported in Japan, 3,6 China, 10 and Korea. 9 The percentages of tumors located in the middle and upper thirds were reported 41.4% and 20.1% in Japan, 6 similar to that reported in China (60.0% in the middle and upper thirds).…”
Section: Discussionmentioning
confidence: 59%
“…1,3 The incidence of gastric cancer in patients younger than 40 years ranges from 2.4% to 6.2%. [3][4][5][6] The clinicopathologic features of gastric cancer in young patients are different from those in older patients. It is considered that higher proportion of young patients have a histologically poorly differentiated type of cancer, female predominance, more aggressive tumor behavior, and metastatic disease at the time of diagnosis than older patients.…”
Section: Introductionmentioning
confidence: 99%